Effect of Preservatives on the Shelf Life of an Indigenous Meat Product: Chicken Chukka - R, Ramani.; Venkataramanujam, V.; Abraham, Robinson J.J.; Rao, V. Appa; Babu , R. Narendra (Journal of Meat Science, 2011)
A study on the shelf - life of an indigenous spent chicken meat product chicken chukka with or without preservatives at room temperature was carried out. The quality parameters like sensory evaluation, pH, moisture per cent, thiobarbituric acid number, tyrosine value (mg/100g), total viable count (log/g) and anaerobic count (log/g) of preservative added (P) and preservative free (NP) chicken chukka samples stored for different periods at room temperature were analysed. There was no significant difference in sensory evaluation scores of both the treatments, due to uniform cooking time and oil temperature maintained during processing. The pH of the samples in both the treatments showed no significant difference. There was a highly significant difference between the two treatments in moisture per cent, thiobarbituric acid number and tyrosine values were significantly higher in preservative free (NP) chicken chukka samples. There was no significant difference observed in the total viable count and anaerobic count of both the treatments. The microbial load was within the safety level up to 28 days of storage in both the treatments. Based on the findings, it is concluded that chicken chukka could be stored up to 28 days under room temperature even without preservatives.
Keywords: Spent hen meat; chicken chukka; preservative; shelf life; room temperature